(untitled) (GYMNASIUM, 2017)
This research starts from the hypothesis that there are individual differences between different types of students (Dureja & Singh 2010). By realizing the present research we have set out to pinpoint the differences between the types of students of "Vasile Alecsandri" University concerning self-confidence and decision making. The current study meant to compare the decision making capacity and the self confidence among students. A total of 200 students of the aforementioned university took part in the study, all aged between 18 and 26 years old. Self-confidence was measured in time while decision making was measured through decision making questionnaires. The T test was used to identify differences between average results of The Vasile Alecsandri University. The level of statistical signification was established to 0.05. The results have shown a significant difference concerning self-confidence which varied between the Phys Ed and other students.